Extended late Holocene relative sea-level histories for North Carolina, \{USA\} - Andrew C. Kemp; Jessica J. Kegel; Stephen J. Culver; Donald C. Barber; David J. Mallinson; Eduardo Leorri; Christopher E. Bernhardt; Niamh Cahill; Stanley R. Riggs; Anna L. Woodson; Ryan P. Mulligan; Benjamin P. Horton (Quaternary Science Reviews, 2017)
Abstract We produced ∼3000-year long relative sea-level (RSL) histories for two sites in North Carolina (USA) using foraminifera preserved in new and existing cores of dated salt-marsh sediment. At Cedar Island, \{RSL\} rose by ∼2.4 m during the past ∼3000 years compared to ∼3.3 m at Roanoke Island. This spatial difference arises primarily from differential \{GIA\} that caused late Holocene \{RSL\} rise to be 0.1–0.2 mm/yr faster at Roanoke Island than at Cedar Island. However, a non-linear difference in \{RSL\} between the two study regions (particularly from ∼0 \{CE\} to ∼1250 CE) indicates that additional local- to regional-scale processes drove centennial-scale \{RSL\} change in North Carolina. Therefore, the Cedar Island and Roanoke Island records should be considered as independent of one another. Between-site differences on sub-millennial timescales cannot be adequately explained by non-stationary tides, sediment compaction, or local sediment dynamics. We propose that a period of accelerating \{RSL\} rise from ∼600 \{CE\} to 1100 \{CE\} that is present at Roanoke Island (and other sites north of Cape Hatteras at least as far as Connecticut), but absent at Cedar Island (and other sites south of Cape Hatteras at least as far as northeastern Florida) is a local-to regional-scale effect of dynamic ocean and/or atmospheric circulation.
Keywords: Salt marsh